1981
DOI: 10.3109/03093648109146227
|View full text |Cite
|
Sign up to set email alerts
|

Surgical footwear in rheumatoid arthritis—a patient acceptability study

Abstract: One hundred patients with rheumatoid arthritis were questioned about the acceptability of the surgical shoes that they had been prescribed for their foot problems. The approach was made from the records of a surgical supplies manufacturer. While 90 per cent experienced good alleviation of symptoms, 50 per cent had complaints regarding fit, comfort and styling. The implications of changes in the supply of shoes and the staffing of orthotic concerns are discussed, and suggestions are made for the direction of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Despite being thought of as being 'satisfied' the females in this study revealed aspects with which they were not satisfied but they demonstrated gratitude for the practitioners' interventions. This appreciation may be what is reported in previous questionnaires as satisfaction [ 8 - 10 ]. This implies that they are not entirely satisfied but feel that they should be grateful for anything even if it is not satisfying all the aspects associated with footwear use.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Despite being thought of as being 'satisfied' the females in this study revealed aspects with which they were not satisfied but they demonstrated gratitude for the practitioners' interventions. This appreciation may be what is reported in previous questionnaires as satisfaction [ 8 - 10 ]. This implies that they are not entirely satisfied but feel that they should be grateful for anything even if it is not satisfying all the aspects associated with footwear use.…”
Section: Discussionsupporting
confidence: 84%
“…The depth of information obtained from these participants has revealed some extremely important issues in addition to what is known from the existing literature that have used more quantitative methods such as questionnaires [ 8 - 10 ]. The interviews have revealed a richness of data about the participants' feelings, perceptions and behaviour with the footwear, particularly in the female group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations